Effect of undergrowth-clearing on evergreen leaf litter decomposition and colonization by microarthropods (PEDOBIOLOGIA, 1996)
The effect of undergrowth-clearing has been studied for two years in a mediterranean Quercus ilex forest. The emphasis has been put on decomposition rate of Quercus ilex leaves placed in nylon bags and on microarthropod populations colonizing the litter bags. Undergrowth-clearing magnifies the characteristics of mediterranean climate but the differences of decomposition rate and microarthropod populations in cleared and uncleared sites are significantly different only in relation to local conditions. In the two situations, the rational and asymptotic models are those which fitted the decomposition rate the best. Seasonal variations of microarthropod populations in the four sites followed the response pattern of these generally observed in mediterranean regions. There was no correlation between litter mass loss and microarthropod numbers in bags. Data of this study were compared with those from nearby areas of Provence or mediterranean xerophilous ecosystems.